PERAN MOTIVASI BELAJAR BAHASA ARAB TERHADAP AKTIVITAS PEMBELAJARAN: STUDI KASUS MAHASISWA PBA UNIVERSITAS MUHAMMADIYAH MALANG - Ahmad Fatoni (El-Tsaqafah : Jurnal Jurusan PBA, 2019)
Arabic language is very important for moslems, through the Arabicteaching throughout the world will increasingly flourish. However, if facedwith the activities within the Arabic learning process, not a few students whohave less motivation in learning activities. This resulted in fewer maximalof Arabic learning processes and in turn will affect student achievement.This research focuses to discuss matters relating to the motivation to learnand student achievement, with the aim of strengthening the importance ofmotivation in the learning Arabic language. The method used is descriptiveanalysis to the students of Arabic Department of Universitas MuhammadiyahMalang. The conclusion from this research is the students have a goodachievement in Arabic learning if it has a well and motivated as well, and thisstudy hopes the Arabic lectures to increase motivation and achievement ofArabic students.